Behaviors Of Leadership In Architectural Offices - Kasapoğlu, Esin (Crc Press-Taylor & Francis Group, 6000 Broken Sound Parkway Nw, Ste 300, Boca Raton, Fl 33487-2742 Usa, 2010)
Leadership can be defined simply as collecting a group of people around definite objectives and having the ability of their achieving these objectives. In architectural offices, as all groups, design group also needs a leader. lithe members of the design team do not trust and believe in the owner of the architectural office, this is a false beginning for construction management process that without being a team achievement of the project can be affected negatively. This study is based on the research in 2008. Data were collected through a questionnaire directed to 40 architects from different architectural offices and discussed through a new model to be effective for the management of the architectural offices. Behaviors of leadership are gathered into two main groups which are delegation of authority and orientation. The common behaviors of the leader architects are aimed to be measured through subgroups of these main groups.